The alleged endemic yellow fever on the coast of Peru - Arce, Julián (1919)
It has been discussed many times in our scientific institutions, whether or yellow fever is not endemic to the coast of Peru, holding at various times and by different observers, and spontaneous generation, ie, the miasmatic origin of that pyrexia in our coast; and its endemicity, consecutive to the first invasion of the scourge that occurred in 1852; and simple post-epidemic of yellow fever germ survival in the form of seasonal sporadic cases, unable to be broadcast without true endemic; and, finally, absolutely denying the endemicity of typhoid yellow on the Peruvian coast.